Investigating the Effects of Storytelling Method on Students’ Memory at Primary Level in (KPK) - Fehmina Anjum (JCTE, 2023)
Methodology bears very concrete role-in the-teaching learning-process to convey any learning material, psychologists and educationists have recommended both cognitive and behavioral methods in this regard. Storytelling method is one of these methods being applied in the classroom teaching. Storytelling involves two-way encounters between a storyteller and one or more listeners. The answers of the listeners affect the plot. In reality, storytelling arises from the engagement and mutual, organized efforts of the storyteller and the audience. This study was aimed at investigating the method of increasing the memory of students of class 4th in the subject of English. Objectives of the study were: (i) to analyze the effectiveness of storytelling method of teaching, (ii) to find out the impact of storytelling method on the memory increase of students, (iii) to explore the motivational effects of storytelling method on students, (iv) to investigate the effects of storytelling method on reading fluency of students. The study population was all girls in Nowshera district primary schools. As a sample of the report, 40 grade 4 students from a Government Girls Primary School were taken. These students were divided into two classes, which were experimental and controlled by random pair sampling on the basis of pre-test and post-test. Pre-test and post-test were used as analysis tools; the data obtained was tabulated and analyzed using t-test and percentage in the light of the study objectives. The analysis of the collected data revealed the following findings. It was concluded from the results that Storytelling method had significant effect on students’ achievement and the learner took interest in the learning. The result of the study showed that storytelling method had significant impact on memory increase of students. Hence it is recommended that teachers may teach elementary subjects through storytelling methods and Government should arrange teacher’s refresher course for storytelling method. It is recommended that teachers should adopt the storytelling method while teaching at elementary level. It was concluded that storytelling method had significance motivational effect on students.